2018
DOI: 10.1103/physrevb.98.094306
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast electron dynamics and orbital-dependent thermalization in photoexcited metals

Abstract: We use a time-dependent density functional theory (TDDFT) to analyze nonequilibrium dynamics of laserexcited electrons in transition metals (Ni, Cr, Cu) and shed light on the ultrafast thermalization process from a microscopical point of view. As a first result, after instant increase of the electron temperature up to 50 000 K, we observe that the dynamics of electron density of states is faster than a laser subcycle, on the attosecond timescale. This is related to an ultrafast rearrangement of excited electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“… 34 ]. Furthermore, first-principles electron dynamics in bulk Cu suggests different electron temperatures for 3 d orbital and 4 s , 4 p orbitlals 35 . As deduced from these facts, it is concluded that conversion of the data obtained from present ab initio results to parameters for the “two temperature model” is not straightforward.…”
Section: Resultsmentioning
confidence: 97%
“… 34 ]. Furthermore, first-principles electron dynamics in bulk Cu suggests different electron temperatures for 3 d orbital and 4 s , 4 p orbitlals 35 . As deduced from these facts, it is concluded that conversion of the data obtained from present ab initio results to parameters for the “two temperature model” is not straightforward.…”
Section: Resultsmentioning
confidence: 97%
“…In these excitations conditions, the optical response remains dominated by the contribution of the bound d-band electrons in agreement with the experimental results (Rmeas  R0). In [15], it is shown that the excitation of a transition metal by an ultra-short pulse leads to the creation of two subsystems of electrons (associated respectively with the d and s/p bands) thermalized to two different temperatures. The equilibrium of the whole electronic system is reached after the end of the pulse, making the TTM inadequate in that case.…”
Section: Tungstenmentioning
confidence: 99%
“…Kinetic models, like the Boltzmann equation 18,[29][30][31][32][33] or Monte-Carlo methods 25,34 allow to trace the evolution of the electronic nonequilibrium. The electronic thermalization 18,[29][30][31][35][36][37] and the influence of the different stages of electronic nonequilibrium distributions on further energy dissipation processes 15,18,[27][28][29]36,38 are in the focus of interest and their details are heavily discussed topics. Recently, also the influence of the nonequilibrium in the phonon system has attracted increasing attention [39][40][41] .…”
Section: Introductionmentioning
confidence: 99%